2008
DOI: 10.1159/000143402
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein, Stem Cells and Cancer: How Study of the Production of Alpha-Fetoprotein during Chemical Hepatocarcinogenesis Led to Reaffirmation of the Stem Cell Theory of Cancer

Abstract: Identification of the cells in the liver that produce α-fetoprotein during development, in response to liver injury and during the early stages of chemical hepatocarcinogenesis led to the conclusion that maturation arrest of liver-determined tissue stem cells was the cellular process that gives rise to hepatocellular carcinomas. When the cellular changes in these processes were compared to that of the formation of teratocarcinomas, the hypothesis arose that all cancers arise from maturation arrest of tissue-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 133 publications
1
53
0
Order By: Relevance
“…Tumor cells synthesize fetal proteins because of the "dedifferentiation" of adult hepatocytes [16] . During fetal life, AFP is synthesized at first by the yolk sac, then by the liver.…”
Section: Afp: What Is It?mentioning
confidence: 99%
“…Tumor cells synthesize fetal proteins because of the "dedifferentiation" of adult hepatocytes [16] . During fetal life, AFP is synthesized at first by the yolk sac, then by the liver.…”
Section: Afp: What Is It?mentioning
confidence: 99%
“…the ability to self renew (Sell, 2009). They resist chemotherapy, persist and then the cancer stem cells reform the cancer (Sell, 2008). There is a parallel between HCC and the rodent oval cell response to the drug DDC, which induces tumor cell formation.…”
Section: Why Do Dysplastic Nodules and Hcc Predominantly Occur When Cmentioning
confidence: 99%
“…Pathologically, AFP is produced and released into the circulation when liver injured or HCC developed, and serum AFP level together with other clinical parameters is widely used as a biomarker for HCC diagnosis or prognosis prediction (Sell, 2008). In this study, we observed that SNP rs9912300 in ACLY gene and SNP rs11871275 in ACACA gene were significantly associated with overall survival of TACE treated HCC patients with lower AFP level and higher AFP level under dominant model, respectively.…”
Section: Discussionmentioning
confidence: 68%